Functional outcome of hindfoot arthrodesis in charcot arthropathy - Kuharajan R; Mohd Yazid Bajuri; Ohnmar H; Yuliawiratman BS (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Charcot arthropathy is a devastating degenerative condition which affects one or more joints that is marked by joint instability, hypermobility resulted from peripheral nerve damage. This was a retrospective study performed on patients who were diagnosed with Charcot arthropathy and those underwent surgery for hindfoot arthrodesis at Universiti Kebangsaan Malaysia Medical Centre from January 2011 until June 2016. The objective of the study was to review the feasibility of an algorithm in managing Charcot arthropathy and to assess functional, clinical and radiographic outcomes of Charcot arthropathy joints treated with hindfoot arthrodesis, at least 6 months follow-up using standardized and internationally accepted scoring systems, which were the American Orthopaedic Foot and Ankle Surgery (AOFAS) score and SF36. A total of 16 patients were included in this study of which 4 (25%) were males and 12 (75%) were females. The mean age was 58.1 (20-71) years. There was equal distribution for side of fusion. We achieved union in 13 out of our 16 (81%) cases followed up. Out of the 3 patients with non-union, 2 were attributed to deep infections. The AOFAS scores for hindfoot and midfoot showed significant improvement post operatively with p-value <0.05 as well as the SF36 mental scores with p-value <0.05. The Physical Component of SF36 showed no improvement. The treatment algorithm currently used in our centre is acceptable and shows good outcomes. While the outcomes are of acceptable rates, efforts should now focus on reducing the complications as the burden of infection and non-union remains a known complication for most bone-related surgeries.